Sustainable learning in the context of repatriated migration to Zimbabwe : trends, opportunities and challenges - Machingambi, Severino (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2026)
This article critically examined the envisaged forced return migration of Zimbabwean nationals who migrated to South Africa because of political and socio-economic turmoil and rising levels of poverty in their country of origin. The research also focused on how the return is likely to impact the sustainable learning and psycho-social well-being of children of school-going age. The push and pull factors model were used as the conceptual frame with which to understand dynamics of migration, including return migration. The data for the study were generated through structured face-to-face interviews with five purposively selected Zimbabwean parents with children of school going age and residing in South Africa. This was triangulated with data obtained through telephonic interviews with five teachers residing in Zimbabwe. The data were coded and analysed thematically and using verbatim statements from the participants. The study established that the anticipated forced return of Zimbabwean migrants would cause disruptions to both continuity of learning and learning outcomes of returnee children at both primary and secondary school. It was also revealed that the return migration posed a major threat to children’s psycho-social adjustment and well-being. The major recommendations include the need to support and capacitate, schools and communities with know-how and resources to re-integrate migrants into educational institutions, home environments and communities.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Volume 10, Issue 1, 2026
Keywords: Return migration; Psychosocial health; Children; Education; Reintegration; Return migration; Emigration and immigration; Health education; Repatriation